Perbaikan Klinis Kaki Diabetik Menggunakan Terapi Akupunktur - Tommy Indra; Dewi Gayatri; Debie Dahlia; Liya Arista (Jurnal Keperawatan Silampari, 2022)
This study aims to identify and analyze the effect of acupuncture therapy on diabetic foot disorders. The design of this study was a systematic review by searching five scientific databases to obtain relevant sources related to specific problems related to acupuncture therapy in reducing disorders of the diabetic foot, namely Pubmed, Scientidirect, Springer Journals, Scopus, and Sage Journals. The research results were 3103 articles, and five articles were relevant and met the criteria. The use of acupuncture therapy affects disorders of the diabetic foot, namely a significant reduction in symptoms such as a prickling sensation or burning feet, numbness, to pain, and as an alternative therapy option in diabetic neuropathy sufferers. In conclusion, acupuncture effectively treats diabetic foot disorders and can be applied to nursing care as a non-pharmacological therapy. Keywords: Acupuncture, Diabetic Foot, Neuropathy